PEMETAAN DAERAH PENGOLAHAN SIRTU DENGAN MENGGUNAKAN TEKNOLOGI UAV PT.CIPTA JAYA MULIA KABUPATEN JAYAWIJAYA PROVINSI PAPUA - Wahyu O. Wakerkwa; Indra Birawaputra (INTAN Jurnal Penelitian Tambang, 2019)
PT. Cipta Jaya Mulia, as a company that has a mining business scope, seeks to increase its production activities. One strategy applied in order to plan additional area of gravel processing location is mapping using drone technology. Mapping using drone can shorten the time of mapping, where this mapping lasts for 80 minutes covering the area mapped by 5 ha with the altitude of flying drones 50 meters above ground level. Drones produce raster data in the form of photos (jpg files) of 1448 photos. The data is then processed using the Agisoft Photoscan software. The unified photos can then be reprocessed in other mapping software like ArcGIS, Global Mapper, and AutoCAD. The mapping results will be used to plan the addition of the gravel processing area of PT. Jaya Jaya Mulia.